EKSISTENSI KEPOLISIAN DALAM KEAMANAN SIBER TERHADAP SEKTOR EKONOMI KREATIF SERTA PARIWISATA DI MASA TRANSISI DIGITALISASI DI KABUPATEN PAMEKASAN: EKSISTENSI KEPOLISIAN DALAM KEAMANAN SIBER TERHADAP SEKTOR EKONOMI KREATIF SERTA PARIWISATA DI MASA TRANSISI DIGITALISASI DI KABUPATEN PAMEKASAN - Moh Akbar Adhiyanto; Muti'ah, Dewi; Habibullah, Abd. Wachid (JUSTITIA JURNAL HUKUM, 2025)
Based on Kaspersky data, there have been 483,980 malicious files targeting business actors in 2023. Seeing this, the role of the Government and the Police has a strategic position in cybersecurity policy efforts for the creative economy and tourism. Pamekasan Regency has potential in the development of the creative economy and tourism, so cybersecurity policies are urgent in the current era of digitalization. This article aims to examine how the role of the Police and the Government in cybersecurity policies is for the creative economy and tourism in the digitalization era. This research was conducted using an empirical juridical method with an exploratory approach. The results of the study show that cybersecurity protection efforts are still not a special concern for the local government and the Pamekasan Regency Police. In addition, policies regarding cybersecurity are still general, which means that they still do not include cybersecurity protection for the creative economy and tourism. Then the results show that the role of the Police is currently only limited to protection on social media (cyberpatrol) and there has been no effort to make cybersecurity policies for the creative economy and tourism sectors. This is influenced by several factors such as the absence of legal regulations, budget limitations, and lack of awareness about cooperation in improving cybersecurity